2016
DOI: 10.1080/03014460.2016.1210675
|View full text |Cite
|
Sign up to set email alerts
|

Is there any association of apolipoprotein E gene polymorphisms with metabolic syndrome in a young population of Croatian origin?

Abstract: Although APOE variants were not confirmed as the risk factor for development of MetS, the APOE alleles were associated with some of the metabolic parameters in young Croatian subjects. The relation of APOE alleles with a concentration of adiponectin and leptin depends on the diet intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…Some studies have been conducted exclusively in the male population with conflicting findings. For example, a small study among young Croatian males revealed no association between any APOE genotype and the prevalence MetS [ 29 ], which was in line with our findings, whereas another study among middle-aged American males found an increased risk of MetS among those with APOE E4 [ 22 ]. We found no studies in a female only cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have been conducted exclusively in the male population with conflicting findings. For example, a small study among young Croatian males revealed no association between any APOE genotype and the prevalence MetS [ 29 ], which was in line with our findings, whereas another study among middle-aged American males found an increased risk of MetS among those with APOE E4 [ 22 ]. We found no studies in a female only cohort.…”
Section: Discussionsupporting
confidence: 90%